Coping Strategies of Students in the Online Teaching and Learning of Physical Education - Davidsol Mendoza (Physical Education and Sports: Studies and Research, 2023)
Background: The emergence of Covid-19 pandemic has brought a lot of changes in the educational system of the country. As the new normal of teaching and learning arose, challenges did the same. There are the teachers and students who must adopt certain adjustments to cope up with the implications of online classroom just to acquire knowledge and reach the target learning without freezing the education. Objectives: This study was conducted with the purpose of determining the problems encountered and the coping strategies of the students in the online teaching and learning of Physical Education. Methods: This study is a descriptive quantitative type of research. Participants were 255 randomly selected students of PE 103-Individual and Dual Sports. In collection of data needed, the researchers utilized a survey questionnaire that contained questions about student’s experiences, students coping strategies, and problems encountered by the students in the online teaching teaching and learning of Physical Education. Results: The results shows that most of the students strongly agreed with the instruction and assessment utilized by their PE instructors; in terms of students coping strategies, most of the students shows less interest in performing physical activities during online classes, and also most of the students engaged in listening to calming music to relax; and in terms of the problems that they have encountered, most of the students experienced problem with their online connections, and most of the students disagree that they have poor comprehensions during online classes. Conclusion: It is concluded that within the experiences of students towards instruction, physical education instructors utilized digital platforms in discussing lessons and gave considerable time for the students to finish and submit all the assigned tasks.  Students had engaged themselves in listening to calming music that helps them avoid stress during online learning but engaged less in doing an activity such as stretching for their physical health. Most of the students highly encountered difficulties towards internet connection during online individual and dual sports but they still have a high comprehension level.